AMYAND’S HERNIA–A RARE CASE OF RIGHT-SIDED INGUINAL HERNIA - Shumenkovski, Velimir; Arnaudov, Dimitar; Trenchikj, Bojan; Antovikj, Svetozar; Ognjenovikj, Ljubomir; Kostovski, Ognen; Volchevski, Goce; Hadzi-Manchev, Dragan; Trajkovski, GJorgji (Macedonian Association of Anatomists and Morphologists, 2023)
Amyand’s hernia is the presence of the appendix in the inguinal hernia sac. The prevalence of this type of inguinal hernia is about 1%. Majority of cases of Amyand’s hernia are incidentally diagnosed during surgical treatment of inguinal hernia. Amyand’s hernia typically presents on the right side since right-sided inguinal hernia is more common and the appendix is located in the lower right quadrant of the abdomen. We present a case of a 23-year-old patient hospitalized at the University Clinic for Digestive Surgery in Skopje for elective surgical treatment of right-sided inguinal hernia.
Keywords: Amyand’s hernia; inguinal hernia; appendix